The Hiring Process and its Automation in Italy - Filippo Bordoni (Labour & Law Issues, 2023)
The hiring process by private employers has faced important changes in the last 30 years, which led companies all over the world, especially the larger ones, to employ various technological tools in this area. For some time, some phases of the hiring process – which is better understood as a sequence of logically coordinated steps through which employers progressively gain insight about prospective employees and decide who to take into further consideration – have been automated through tools based on artificial intelligence. Once the ever-changing AI applications in this field are classified using a generally applicable scheme, it will be possible to focus on the Italian and international market for the software used to automate the hiring process. This kind of technology makes room for numerous legal implications: in particular, concerns about the right to data protection, the right to not be discriminated and, more generally, the right to work seem reasonably founded.